Plan for Peace - Labour Party pamphlet, 1945 (1945)
1945 1939-1945 "Plan for Peace - Labour Party pamphlet, 1945" [HFR0070], 1945 Plan for peace, written by Ellen Wilkinson and published after VE Day in the Summer of 1945, sets out the Labour Party's initial programme for post war reconstruction.